Pop Art : Object and image - Finch, Christopher (London : Studio Vista, 1968)
Duchamp, Marcel ; Lichtenstein, Roy ; Oldenburg, Claes ; Poussin, Nicolas ; Rauschenberg, Robert ; Warhol, Andy ; etc.
Engels
boek